Determination of L-Phenylalanine in Human Plasma Samples with New Fluorometric Method - Sari, Tolga; Dede, Sureyya; Yusufoglu, Busra; Karakus, Emine (SPRINGER, 2022)
The measurement of phenylalanine in biological fluids for the diagnosis of phenylketonuria (PKU) in newborns and the monitoring/therapeutic drug monitoring of individuals with PKU are especially important. Owing to the importance of PKU monitoring in clinical medicine, a new fluorometric method was developed for the determination of L-phenylalanine in serum samples. This method is based on the relationship between phenylalanine ammonia-lyase (PAL) and o-phthalaldehyde (OPA). PAL catalyzes the conversion of phenylalanine to ammonia and trans-cinnamic acid. The formed ammonia reacts with OPA in the presence of sodium sulfite, giving a fluorescent product. The presence of sulfide in an alkaline environment prevents OPA from reacting with other amino acids while allowing it to react only with ammonia. Method characterization and optimization studies, such as the effects of pH, temperature, and interferents, were carried out. The amount of L-phenylalanine in a human serum sample was successfully determined by using the fluorescence emission intensity of the fluorescent product formed as a result of the reaction between OPA and ammonia. The linear range of the method is between 10 mu M and 10 mM. The obtained result showed good agreement with the results of the biochemistry analysis laboratory. Recoveries of 95.41% and 73.39% were obtained for phenylalanine and ammonia, respectively. This PAL-OPA-based fluorometric method for phenylalanine is practical, easy to operate, low cost, highly sensitive, and selective and can also be used for the simultaneous determination of ammonia in human serum samples.
Keywords: L-Phenylalanine; Phenylalanine ammonia-lyase; o-Phthalaldehyde; Fluorometry; Phenylketonuria; POLYETHYLENE-GLYCOL; BIOSENSOR; DIAGNOSIS; TYROSINE; ASSAY; HPLC; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology